1970
DOI: 10.5424/sjar/2010084-1382
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for biodiesel in Spain: a pilot study for diesel consumers

Abstract: One of the priorities of the European Union is to reduce greenhouse gas emissions in order to contribute significantly to climate change mitigation. The aim of this paper is to analyze consumers’ valuation of one type of renewable energy which is important to reach the European emission reduction targets, biodiesel, and to assess the extra price consumers are willing to pay to use biodiesel instead of conventional diesel. In order to achieve these goals, a market survey has been carried out in Aragón (Spain) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
5
13
2
Order By: Relevance
“…The sample size is consistent with most literature on the topic including studies mentioned in the article, or even larger(Giraldo et al, 2010;Li and McCluskey, 2014;Salvo and Huse, 2013), although there are also works based on larger samples exceeding one thousand respondents(Jensen et al, 2010;Solomon and Johnson, 2009).P. Lanzini et al / Journal of Cleaner Production 112 (2016) 2684e2692…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The sample size is consistent with most literature on the topic including studies mentioned in the article, or even larger(Giraldo et al, 2010;Li and McCluskey, 2014;Salvo and Huse, 2013), although there are also works based on larger samples exceeding one thousand respondents(Jensen et al, 2010;Solomon and Johnson, 2009).P. Lanzini et al / Journal of Cleaner Production 112 (2016) 2684e2692…”
supporting
confidence: 78%
“…As regards biodiesel in Europe, empirical evidence is scant and inconclusive. While for instance Giraldo et al (2010) suggest that Spanish consumers have an average WTP for biodiesel of around 5 eurocents per liter (0.054V), Kallas and Gil (2014) found that drivers in Catalonia are not willing to pay any premium for biodiesel.…”
Section: Biofuels: Overview and Consumers' Wtpmentioning
confidence: 99%
“…cars are not willing to pay for biodiesel, which seems to be rejected in all the mixtures 499 proposed; this result is contrary to the results obtained by [6], who confirmed that consumers 500 are willing to pay 0.08 Euros/litre and [41] who determined that Spanish users of diesel are 501 willing to pay up to 5% over the price of standard diesel. 502…”
contrasting
confidence: 56%
“…The biofuel industry in 2011 was supported 153 with €237 million for ethanol and €1,002 million for biodiesel [26] Jeanty et al [39], and Jeanty and Hitzhusen [40] estimated the WTP for the reduction of air 163 pollution, which is brought about by using biodiesel in the US. In Spain, Giraldo et al [41] and 164…”
mentioning
confidence: 99%
“…In other for biofuel project to be achievable and successful, sufficient information and planning is required to actualize its benefits. It is necessary to know how households' value and support renewable energy source in this case biofuel gel and their Willingness To Pay (WTP) a reasonable price for it is a relevant issue [13].…”
Section: Introductionmentioning
confidence: 99%